The Dichotomization of Objective and Subjective Outcome Measures of Academic Performance in an Online Learning Environment - Aperapar Singh, Parmjit Singh; Anthonysamy, Lilian (Universiti Utara Malaysia Press, 2023)
Purpose – Various recent studies are perplexed with the situation if subjective measures such as perceptions of learning reflect knowledge gains and whether they can be used as a surrogate for evidence of actual learning in an online learning environment. Due to a rising trend in current research studies interpreting perceptions of learning compared to actual learning as a measure of success, this study investigates the dichotomous measures of objective and subjective measures of academic performance in an online learning environment with selected predicted variables. This is followed by an investigation on the effect of online learning on students’ academic performance prior to and during the Covid environment.